Nutrition in pediatrics (B.C. Decker, 1997)
The book offers a comprehensive approach to nutritional practices in the care of infants and children. first, the book presents general concepts of nutrition, such as nutrient requirements, nutritional assessment, and prevetion of disease; Second, it develops a systematic approach to the pathophysiology of nutrition as it pertains to other disciplines - immunology, endocrinology, pharmacology, and gastroenterology. Third, it covers specific disease states and is directed at the nutritional management of these conditions, which include diabetes, cystic fibrosis, and anemias. Thus, it provides updated information on the unique nutritional needs of patients with these diseases, these chapters are augmented by appropriate appendix material describing special diets and requirements of patients. Finally, the book presents an approach to nutritional support of pediatric patients, a major effort is directed at updating the reader on the more recent information about breast-feeding. Following a practical discussion concerning problems of nursing mothers, the book addresses enteric and parenteral support of pediatric patients with special needs for nutritional support